Synthesis, Characterization and Crystal Structure of 4-Dichloroacetyl-2,5-dimethyl-8-oxo-1,4-diazabicyclo[3.3.0]octane - Fu, Ying; Xu, Zhao-Zheng; Ye, Fei (Asian Journal of Chemistry, 2014)
4-Dichloroacetyl-2,5-dimethyl-8-oxo-1,4-diazabicyclo[3.3.0]octane was synthesized by cycloaddition and acylation reaction. The molecular structure was characterized by IR, NMR, MS, elemental analysis and further confirmed by X-ray diffraction analysis. The title compound, C10H14N2O2Cl2, crystallized in the monoclinic P21/c space group with unit cell parameters a = 10.286(2) Å, b = 11.513(2) Å, c = 12.234(5) Å, Z = 4, V = 1223.5(6) Å3, Dc = 1.439 g/cm3, F (000) = 552, R1 = 0.0405 and wR2 = 0.1020. In the crystal structure, the molecule was linked through intermolecular C(7)-H(7)...O(2) hydrogen bond forming a one dimension chain conformation.